2017
DOI: 10.1177/1010428317706918
|View full text |Cite
|
Sign up to set email alerts
|

IL-36α suppresses proliferation of ovarian cancer cells

Abstract: Interleukin-36α (IL-36α), also formerly known as IL-1F6, is pertaining to IL-1 family members that has been shown to play an important pro-inflammatory role in chronic immune disorders. However, the role IL-36α in the setting of cancer remains unknown. Here, in our study, to investigate the clinical relevance of IL-36α in ovarian cancer, clinicopathological significance as well as expression level of IL-36α were analyzed in epithelial ovarian cancer clinical tissues and paired normal control. To explore the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
(28 reference statements)
2
23
0
Order By: Relevance
“…Specifically, we validated melatonin action on two genes involved in the immune response and tumor progression. Il1f6 shows an important pro-inflammatory role in chronic immune disorders 58,59 and recently its role in cancer has been described 59,60 . This gene is a member of the IL-1 family of cytokines, also composed of two other agonists, IL-36-β (IL-1F8) and IL-36γ (IL-1F9) and one antagonist IL-36Ra (IL-1F5) 61,62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we validated melatonin action on two genes involved in the immune response and tumor progression. Il1f6 shows an important pro-inflammatory role in chronic immune disorders 58,59 and recently its role in cancer has been described 59,60 . This gene is a member of the IL-1 family of cytokines, also composed of two other agonists, IL-36-β (IL-1F8) and IL-36γ (IL-1F9) and one antagonist IL-36Ra (IL-1F5) 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al . showed that IL-36 gene therapy can inhibit the growth in xenograft model of epithelial ovarian cancer 59 . Moreover, its upregulation was able to regress the tumor masses in fibrosarcoma mouse model and reduce the Ki-67 expression 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining members of this family, IL-36α and IL-36β, to date, three studies in the literature have suggested that IL-36α may also have tumor-suppressive effects. IL-36α was shown to suppress the growth of ovarian cancer cells (120). Moreover, reduced expression of IL-36α has also been shown to be associated with poor prognosis in colon (121) and hepatocellular cancer (122).…”
Section: Interleukin-36mentioning
confidence: 99%
“…IL-36γ is a recognized T-bet target in myeloid cells, and T-bet can instigate decreases in tumor growth by promoting dendritic cell (DC)-mediated ectopic lymphoid organogenesis in a manner that is dependent on IL-36γ (101, 102). There is the mounting evidence that suggests IL-36 cytokines can act as tumor suppressors, although it is yet to be deciphered whether this function has any connection to angiogenic regulation (103, 104).…”
Section: Il-36 Il-37 and Il-38—the Story Emerging So Farmentioning
confidence: 99%